Advances in Membrane Development Based on Electrically Conducting Polymers. Issue 1 (28th February 2012) - Alam, Javed; Dass, Lawrence Arockiasamy; Alhoshan, Mansour Saleh; Mohammad, Abdul Wahab
Abstract The use of electrically conducting polymers for membrane development is an interesting research area of membrane science and technology. Electrically conducting polymers have been identified as a promising class of materials for membrane development owing to their unique electroactive properties, reversible redox behavior, and the potential for ease of processing. In the present review, an attempt has been made to describe the advances in the use of electrically conducting polymers to membrane development and to understand their salient features and how these features can be optimized to exhibit advanced or novel functions in membrane development. This article also presents significant literature detailing the scientific interest in electrically conducting polymers for membrane development. © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E189–E197, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21262